Konstytucja kadyska z 1812 r.: kontynuacja czy zerwanie z tradycją? - Jakóbczyk, Patrycja (Acta Universitatis Lodziensis. Folia Historica, 1999)
The Constitution of Cádiz, promulgated on March 19, 1812, was the first modern code of the Spaniard. It consists of 384 articles collected in 10 titles of various longeness. This main work of the Cortes of Cádiz was a victory of the liberal groups whose aim was to take away the initiative of the reforms originated in Bayonne by the French, as well as to build new political system and to cause social transformation. The Constitution was based on three essential principles: a) national sovereignty. The supreme power which had belonged thus far to King, now was given to the Nation, b) division of powers. The right to legislate was safeguarded both to Cortes and King, to execute to King and to judge to independent tribunals, c) new national representation. The deputies didn’t represented from now on neither classes nor their electors but the nation on the whole. But the Constitution didn’t break with national tradition and their authors distinctly appealed to the mediaeval Spanish institutions, that is both moderate monarchy and Cortes. The catholic religion also kept its entire domination. This way the authors intended to make agree that what was revolutionary with tradition. The Constitution was repudiated on May 14, 1814, right away after the return of Ferdinand VII. It was in force yet twice for a short time: in 1820-1923 and 1836 and it became an ideal or model for Spanish Liberals in XIX century.